Lessons learned from the “Goodie Box”: A message design study developed and evaluated in community settings for cervical cancer prevention - McFarlane, Soroya Julian; Morgan, Susan E.; Carcioppolo, Nick (Frontiers in Oncology, 2022)
Despite the availability of free pap testing services, Jamaican women have low human papillomavirus (HPV) screening rates; 16% of women in the Kingston Metropolitan Area have been screened within the prior 3 years. This paper discusses the testing of theory-based messages to increase HPV screening uptake in a low resource setting, using HPV self-test kits designed for this intervention. A total of 163 Jamaican women, aged 30–65 years, who had not had a pap test in at least 3 years, from two low socioeconomic status communities in Kingston, were enrolled and assigned to one of two versions of an HPV self-test kit, either with or without culturally-targeted, fear appeal messages. The uptake of screening was high across conditions; 95.6% of participants used the HPV self-test and returned their kits. However, surprising variations were observed in self-test acceptability, explained by differing attitudes toward the message conditions. Based on the results, we recommend 4 key components to increase HPV screening in low-resource settings: 1) focus on perceived threat in message design 2) avoid written materials due to literacy concerns 3) use culturally-appropriate interpersonal or community-based channels 4) consider alternative solutions (such as a self-test) available at no or low cost to address structural barriers.